Cloud Transformation in Financial Services: A Strategic Framework for Hybrid Adoption and Business Continuity - Sreenivasulu Gajula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the strategic adoption of cloud computing technologies within the financial services sector, focusing on the implementation of hybrid cloud architectures that balance innovation with regulatory compliance. The article explores how financial institutions can leverage cloud solutions to enhance disaster recovery capabilities and business continuity while maintaining strict security protocols for sensitive financial data. The article analyzes the transition toward cloud-native development methodologies, including microservices and containerization, as catalysts for digital transformation in banking and finance. The article presents an enterprise architecture framework that guides financial organizations through their cloud migration journey, addressing the complexities of integrating legacy systems with modern cloud infrastructures. The findings suggest that a well-orchestrated cloud strategy can significantly improve operational resilience, reduce time-to-market for new financial products, and create sustainable competitive advantages while navigating the unique regulatory landscape of the financial services industry.